Intravenous amino acids for kidney protection in patients undergoing cardiac surgery: A systematic review and meta-analysis of randomized controlled trials - Malik Waleed Zeb Khan; Aizaz Ali; Amna Hussain; Aban Masaud Mian; Abdul Moeez; Waqas Inayat; Bushra Noor; Izhar Ali Shah; Muhammad Osama; Bushra Khan; Muhammad Sajid; Touba Azeem; et al. (Journal of International Medical Research)
Objective To evaluate the efficacy of intravenous (IV) amino acids in preventing acute kidney injury (AKI) in patients undergoing cardiac surgery. Methods PubMed, EMBASE, and Cochrane Library databases were systematically searched for all relevant randomised controlled trials (RCTs) published from inception to July 25, 2024. A random effects model was used to pool the risk ratios (RR) for dichotomous outcomes, and the combined data was visually represented using forest plots. Results 3 studies involving 3646 patients were included in the meta-analysis. IV amino acids did not significantly lower the overall AKI incidence compared with control measures. However, they significantly reduced the risk of Stage 1 AKI and Stage 3 AKI. No differences were observed between intervention and control for Stage 2 AKI or need for kidney replacement therapy. Conclusion IV amino acids may offer protective benefits against severe AKI stages in cardiac surgery patients. Further studies are warranted to validate our findings.